2006
DOI: 10.1021/om0608004
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Hydroallylation of Activated Alkenes

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…Compound 27 after desilylation using TBAF and KOH furnished diene 28 in 80% yield. Finally, diene 28 upon reaction with molecular oxygen in the presence of Rose Bengal in EtOH resulted in cyclic peroxide, which was reduced in situ with NaBH 4 to give peribysin D. 21 All of the spectral data, including 1 H and 13 C NMR data, were in agreement with the literature report. 17 It was clear from our previous work that the structure of peribysin D may need to be stereochemically revised (see ref 4).…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Compound 27 after desilylation using TBAF and KOH furnished diene 28 in 80% yield. Finally, diene 28 upon reaction with molecular oxygen in the presence of Rose Bengal in EtOH resulted in cyclic peroxide, which was reduced in situ with NaBH 4 to give peribysin D. 21 All of the spectral data, including 1 H and 13 C NMR data, were in agreement with the literature report. 17 It was clear from our previous work that the structure of peribysin D may need to be stereochemically revised (see ref 4).…”
supporting
confidence: 83%
“…In addition, fluoride- and alkoxide-based reagents were unsuccessful in the desilylation reaction (Table , conditions 5–7) . The use of HMPA along with TBAF as reported by Muraoka et al gave an ∼20% yield of the desired product . Capperucci et al have reported a condition under which TBAF and KOH were used in combination for the proto-desilylation of the triphenyl silyl group .…”
mentioning
confidence: 99%
See 1 more Smart Citation